Maritime Accident Risk Assessment as a Basis for Selecting Anchorage Area Locations: A Perception Study in the Waters of Riau Islands, East Kalimantan, and South Kalimantan - Raden Aditya Wirawan (Siber Journal of Transportation and Logistics, 2026)
This study aims to analyze stakeholder perceptions regarding the risk of shipping accidents as a basis for consideration in selecting locations for anchorage areas to be commercialized in the waters of Riau Islands (Kepri), East Kalimantan (Kaltim), and South Kalimantan (Kalsel) Provinces. The method used is a descriptive quantitative and qualitative survey of 39 respondents consisting of representatives from the Ministry of Transportation (56.4%), Local Government (15.4%), Associations (7.7%), the Private Sector (15.4%), and Academics (5.1%). The survey results indicate that the majority of respondents (71.8%) stated that the marine location significantly influences the risk of shipping accidents. Marine environmental conditions were deemed highly influential by 79.5% of respondents, and 84.6% of respondents stated that a combination of extreme conditions (storms, high waves, and strong currents) constitutes the primary threat. From a shipping traffic perspective, 82.1% of respondents selected a combination of congested conditions, narrow waters, and the absence of Aid to Navigation (AtoN) as the greatest potential risk. Regarding anchoring, 97.4% of respondents agreed that the designation of these areas needs to be carried out by the government, and 79.5% designated the Ministry of Transportation as the authorized organizer. Furthermore, 87.2% of respondents supported the Public-Private Partnership (PPP) scheme, with Concession and Utilization Cooperation (KSP) being the preferred options at 41% each. The urgency of risk assessment in location selection obtained an average score of 4.26 on a scale of 5, while the value of safety as an investment parameter reached an average of 4.64.